2019
DOI: 10.1080/1331677x.2019.1627894
|View full text |Cite
|
Sign up to set email alerts
|

Bank-specific and macroeconomic determinants of non-performing loans in the Republic of Macedonia: Comparative analysis of enterprise and household NPLs

Abstract: The purpose of this paper is to explore the influence of bankspecific and macroeconomic determinants of all non-performing loans (NPLs) to enterprises and households in the Republic of Macedonia. The analysis is performed for the whole banking sector for the period 2003Q4 to 2014Q4, by applying the Autoregressive Distributed Lag Modelling Approach (ARDL), the co-integration model implementing quarterly time series. The results of the research indicate that the profitability of banks, the growth of loans to ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 38 publications
9
65
1
12
Order By: Relevance
“…At this stage the bank has to recognise all credit losses that will occur if default occurs within 12-months. The amount of non-performing loans is related to bank-specific and macroeconomic determinants (Kjosevski, Petkovski & Naumovska, 2019). Expected credit loss is therefore estimated on all available information such as bank's actual credit loss experience, forward looking information on payment status and macroeconomic variables (GDP growth, changes in unemployment rate, property prices etc.).…”
Section: Transition To Ifrsmentioning
confidence: 99%
“…At this stage the bank has to recognise all credit losses that will occur if default occurs within 12-months. The amount of non-performing loans is related to bank-specific and macroeconomic determinants (Kjosevski, Petkovski & Naumovska, 2019). Expected credit loss is therefore estimated on all available information such as bank's actual credit loss experience, forward looking information on payment status and macroeconomic variables (GDP growth, changes in unemployment rate, property prices etc.).…”
Section: Transition To Ifrsmentioning
confidence: 99%
“…Kjosevski [31] conducted sector-wise research and found NPLs of both the enterprise and household were negatively sensitive to profitability, loan growth, and better economic conditions while banks' solvency and unemployment were positively correlated. The authors of [19] examined NPLs determinants in the Eurozone and, like past examinations, found bank-specific and macroeconomic elements had a remarkable impact clarifying variations in NPLs [32,33].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Loan Growth Rate (Zheng, Bhowmik, & Sarker, 2019); Capital Adequacy Ratio (CAR) (Kjosevski, Petkovski, & Naumovska, 2019); Income Diversification (Templeton & Severiens, 1992;Winton, 1999); Liquidity Ratio (Manab, Theng, & Md-Rus, 2015); Bank Credit Growth (Shkodra & Ismajli, 2017;Vithessonthi, 2016) and Operating Expenses and Bank Size (Gulati, Goswami, & Kumar, 2019;Sufian & Noor, 2012).…”
Section: Credit Risk (Cr) and Its' Sourcesmentioning
confidence: 99%